The Interplay Between Economic Status and Attractiveness, and the Importance of Attire in Mate Choice Judgments - Gouda-Vossos, Amany; Brooks, Robert C.; Dixson, Barnaby J. W. (Frontiers in Psychology, 2019)
Desirable characteristics of ‘opposite sex others’, such as physical attractiveness and economic status, can influence how individuals are judged. However, whether modifying economic status influences ratings of attractiveness differently in women and men remains to be determined. In two studies, ratings of economic status and attractiveness were quantified for male and female targets that were presented under various social contexts. Study 1 assessed judgments (n = 1359) of images of nine male and nine female targets in different sized groups containing only opposite-sex others (i.e. group size). While we found no significant effects of group size on male and female attractiveness, target female economic status increased when surrounded by two or more men. An ad hoc analysis controlling for the attire of the targets (Business or Casual) found that the association between target female economic status and group size occurred when females were in business attire. Study 2 investigates this effect further by presenting images of twelve males and twelve females, in higher and lower status attire (i.e. Business and Casual clothing) and measured judgements of attractiveness and economic status among women and men (n = 1038). Consistent with the results of Study 1, female economic status was only affected when women were in business attire. However, female economic status decreased when in the presence of other men in business attire. There were no sex differences in judgments of economic status when judging stimuli in casual attire. Additionally, negative associations between attractiveness and economic status were found for males presented in casual attire. We discuss these results in the light of evolutionary sexual conflict theory by demonstrating how the asymmetrical importance of status between men and women can influence mate choice judgments.